ON THE OCCURRENCE OF FISH LARVAE IN THE MANORA CHANNEL, KARACHI - Khan, J Ali; Waqar, Talat (Indian Journal of Fisheries, 2011)
A study based on surface samples collected from three fixed stations overthe years 1968-70 shows that the ichthyoplankton is very poor in the Manorachannel obviously because, with considerable waste materials introduced from theiishing harbour, the oil and sewage from large number of ships and boats andthe discharge received from the Lyari river, to which the sewerage system ofKarachi city is linked, the channel is now unfit to sustain a larval fish populationof any magnitude. The fish larvae, mainly belonging to 24 identified families,are being brought into the channel with the tidal flow, ideally when the tidalheight is 2-2.5 m. But these larvae, especially the smaller ones, return back withthe tide, and whatever larvae remain are either confined to the lower harbouror suffering mortality.The yearwise and seasonwise distribution of the larvae of the variousfamilies are given along with graphs